2013
DOI: 10.1051/0004-6361/201321285
|View full text |Cite
|
Sign up to set email alerts
|

A line confusion-limited millimeter survey of Orion KL

Abstract: Context. We present a study of the sulfur-bearing species detected in a line confusion-limited survey towards Orion KL performed with the IRAM 30-m telescope in the frequency range 80−281 GHz. Aims. This study is part of an analysis of the line survey divided into families of molecules. Our aim is to derive accurate physical conditions, as well as molecular abundances, in the different components of Orion KL from observed SO and SO 2 lines. Methods. As a starting point, we assumed local thermodynamic equilibri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 79 publications
(70 reference statements)
9
66
0
Order By: Relevance
“…As a result, the SO 2 /SO ratio increases with time, in agreement with the results obtained by Wakelam et al (2011), who modelled the sulphur chemistry of several massive dense cores. This is also consistent with Esplugues et al (2013a), who concluded that SO 2 is a better tracer of warm gas than SO. For longer times, t 8 × 10 4 years since the star switches on, the increase in SO 2 starts to be limited as the reaction…”
Section: Sulphur Chemical Evolution In the Hot Coresupporting
confidence: 91%
“…As a result, the SO 2 /SO ratio increases with time, in agreement with the results obtained by Wakelam et al (2011), who modelled the sulphur chemistry of several massive dense cores. This is also consistent with Esplugues et al (2013a), who concluded that SO 2 is a better tracer of warm gas than SO. For longer times, t 8 × 10 4 years since the star switches on, the increase in SO 2 starts to be limited as the reaction…”
Section: Sulphur Chemical Evolution In the Hot Coresupporting
confidence: 91%
“…To obtain a good fit to the lines at low frequencies, we also considered a contribution from the extended ridge, with a column density of N(HC 3 N) = (8 ± 2) × 10 13 cm −2 . In addition, similar to the analysis of SO and SO 2 emission in Esplugues et al (2013), we also found a contribution from the component centered at 20.5 km s −1 , with N(HC 3 N) = (3.4 ± 0.6) × 10 14 cm −2 . This contribution is negligible in the isotopologues or vibrational modes of HC 3 N, but it is significant for ground-state transitions, as we can see in the line profiles in Fig.…”
Section: Hc 3 Nsupporting
confidence: 87%
“…To apply the LVG code, we considered the same cloud components for Orion KL as were used in Esplugues et al (2013) for the analysis of SO and SO 2 . Most of these cloud components were also considered in previous Orion KL interferometric studies such as those of Wright et al (1996) and Beuther et al (2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The millimetre wavelength window is important for studying massive star formation, because it contains many useful molecular probes, such as shock tracers (SiO, SO, HNCO and H 2 CO; Schilke et al 1997;Esplugues et al 2013;Rizzo, Fuente & García-Burillo 2005), long carbon chain molecules (c-C 3 H 2 , HC 3 N and HC 5 N; Morris, Snell & vanden Bout 1977;Chung, Osamu & Masaki 1991;Bergin, Snell & Goldsmith 1996), deuterated molecules (DCN, DCO + , C 2 D and NH 2 D; Shah & Wootten 2001;Pety et al 2007;Parise et al 2009) and dense gas traces (HCN, HCO + , CS and C 2 H; Padovani et al 2009), etc.…”
mentioning
confidence: 99%